Intellectual capital and corporate value of listed firms in Nigeria : moderating role of board diversity - Mutalib, Anifowose (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Global economy has, in the last two decades, witnessed some transformations. The principal among them is changing from the tangible production processes to intangible one tagged as knowledge-based economy where intangible asset has been considered as the main instrument of competitive advantages at both micro and macro levels. However, the extent to which this strategic resource has impacted corporate value remain unclear as most studies are limited to traditional accounting performance indicators. Thus, this study investigates the relationship between intellectual capital and corporate value moderated by ethnic diversity and religious diversity of board of director in Nigeria over a period of 2010 to 2014 using panel data analyses. The study is based on quantitative data obtained from 91 companies' annual reports and accounts, and supported with qualitative data using semi-structured interviews conducted with ten financial analysts and ten heads of accounts of listed firms in Nigeria. The findings from the analyses of the two-step system generalised method of moment (GMM) estimator and qualitative empirical investigation through face-to-face personal interviews were used to achieve the research objectives and answer the research questions advanced in the study. Twelve hypotheses are advanced based on resource based, signalling and upper echelons theories. While some of the findings were in line with theoretical expectations, others were found not to support the hypotheses formulated. The overall findings show that intellectual capital performance improves corporate value among listed firms in Nigeria in the period under study. The study also found that intellectual capital disclosure reduces the degree of share price volatility while it fails to significantly explain the corporate cost of capital. It was also found that ethnic diversity and religious diversity have favourable significant impact on the relationship between intellectual capital and corporate value of listed firms in Nigeria. The findings of the study have both theoretical as well as policy implications. In terms of theoretical implications, the use of upper echelons theory is supported by the findings of this study. Thus, this proves that board diversity along ethnic and religious lines can be used as a moderating factor in the intellectual capital accounting research. In terms of policy implications, the fact that board diversity moderated the relationship between intellectual capital and corporate value poses some regulatory questioning. Hence, there is a need for regulatory agencies to be more proactive in ensuring the appropriate mixture in the board room along ethnic and religious lines. Notwithstanding several limitations inherent in the study, the study contributes to the intellectual capital accounting research paradigm by employing relevant value related dependent variables as well as ethnic diversity and religious diversity as moderating variables together with the consideration of endogeneity based on the estimator approach adopted.